Analisis Daya Tarik Iklan Gopay Pada Media Youtube Versi “Pevita Ditembak, Jota Bertindak” - Shinta Hartini Putri; Resa Dini Ramadhani (ArtComm, 2020)
As one form of mass communication, advertising becomes a means of communication that contains information products (goods or services) that are persuasive from a company or non-personal institution to achieve marketing strategies. The ability of advertising in forming brand image makes companies competing to create ads that have an attractive visualization but do not rule out the message of the product. This is also the case with the Gopay e-money application, one of the digital financial products owned by PT. Karya Anak Bangsa has succeeded in creating advertisements that are able to visualize product messages with good animation accompanied by the selection of Pevita Pearce and Joe Taslim as the right ambassador brands. The purpose of this study is to explain how Gopay is able to make ads that are able to be both attractive in the aspects of the message content to the ambassador brand in the ad. The results of this study are to see how advertising and brand ambassadors can influence consumer brand awareness of Gopay. This research method uses literature study by collecting data from articles, scientific journals and theses related to the topics under study.